Coastal Environmental Factors Related to the Increase in ISPA Cases at the Belawan Branch Health Center - Nofi susanti; Natasya Aulia; Fatimah Zuhra; Miftahul Nur Zahrah; Syfa Ardhia Putri; Alifa Fatiha (International Journal of Health, Economics, and Social Sciences (IJHESS), 2026)
Acute Respiratory Infection (ARI) is still a public health problem that is often found in coastal areas, including in the work area of the Belawan Branch Health Center, Medan City. Characteristics of the coastal environment such as air quality influenced by port activities, settlement density, housing conditions, high air humidity, and environmental sanitation are suspected to play a role in the increase in ISPA incidents. This study aims to describe the distribution of ISPA incidence based on coastal environmental factors in the work area of the Belawan Branch Health Center. This study uses a quantitative approach with a descriptive analysis method. The research sample amounted to 100 respondents who were selected using accidental sampling techniques. Data collection was carried out through interviews using structured questionnaires and observation of the environmental conditions of the respondents' residences. The variables studied include environmental air quality, settlement density, house ventilation, environmental humidity, and environmental sanitation. The data is analyzed descriptively and presented in the form of frequency and percentage distributions. The results showed that the proportion of ISPA incidence was higher in respondents living in environments with poor air quality, dense settlements, unqualified home ventilation, high environmental humidity levels, and poor environmental sanitation. This condition reflects the important role of coastal environmental factors in the incidence of ISPA in the research area. The conclusion of this study shows that coastal environmental factors contribute to the high incidence of ISPA in the work area of the Belawan Branch Health Center. Therefore, efforts to prevent ISPA need to be focused on improving environmental conditions and strengthening promotive and preventive activities at the primary health service level.